2023
DOI: 10.1002/jcc.27119
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation of the lead‐free double perovskites halides Rb2XCl6 (X = Se, Ti) for optoelectronic and thermoelectric applications

Abstract: In this study, structural, electronic, optical, thermoelectric, and thermodynamics properties of vacancy‐ordered double perovskites Rb2XCl6 (X = Se, Ti) were explored theoretically. The results revealed that Rb2SeCl6 and Rb2TiCl6 are indirect band gap (Eg) semiconductors with Eg values of 2.95 eV, and 2.84 eV respectively. The calculated properties (phonons, elastic constant, Poisson's ratio, and Pugh's ratio) revealed that both materials are dynamically and chemically stable and can exhibit brittle (Rb2SeCl6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The positive values up to a wide range of energy reflect the semiconductor behavior of both DPs. 49 In some regions, ε 1 (0) has negative values. In these regions, a material behaves like a perfect metal.…”
Section: Resultsmentioning
confidence: 99%
“…The positive values up to a wide range of energy reflect the semiconductor behavior of both DPs. 49 In some regions, ε 1 (0) has negative values. In these regions, a material behaves like a perfect metal.…”
Section: Resultsmentioning
confidence: 99%
“…It is confirmed that ionic bonding exists in these compounds by the positive Cauchy pressure values found for A 2 TlAgF 6 (A = Rb, Cs). Another crucial factor that can be used to alter material characteristics on the makeup of microcracks is elastic anisotropy (A) 57 . Anisotropic materials must be presumed if the unity value deviates.…”
Section: Resultsmentioning
confidence: 99%
“…The thermoelectric performance of the materials under investigation has been evaluated using the figure of merit ZT = σS 2 T / κ . For effective thermoelectric materials, high Seebeck coefficients ( S ) and electric conductivity ( σ ) are preferred, while low thermal conductivity ( κ ) is considered ideal 57 . In the current study, we use the BoltzTraP code that is applied under constant relaxation time approximation 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, this cubic phase is thermodynamically stable because the calculated values of formation energy (E f ) (Table 2) have the negative values according to the condition for thermodynamic stability. [33] The dynamical stability is another important criterion for use of a compound in the devicebased applications. Therefore, we examined the chalcogenidebased Ba 2 MgXO 6 for dynamical stability from phonon dispersion spectra, where, from these spectra in Figure 2, it can be seen that the phonon frequencies are positive throughout the considered Brillouin zone.…”
Section: Structural Propertiesmentioning
confidence: 99%